Use of Active Workstations in Individuals with Overweight or Obesity: A Systematic Review. Issue 3 (5th February 2019) - Josaphat, Kapria‐Jad; Kugathasan, Thiffya Arabi; E.R. Reid, Ryan; Begon, Mickael; Léger, Pierre‐Majorique; Labonté‐Lemoyne, Elise; Sénécal, Sylvain; Arvisais, Denis; Mathieu, Marie‐Eve
Abstract : Objective: This systematic review aims to collect existing literature and summarize the impact of active workstations on the health and work outcomes of participants with overweight or obesity. Methods: Five databases were examined (until March 2018), and the keywords "desk, " "workstation, " "work station, " and "work stations" were used with any one of the following terms: "active, " "bik*, " "cycling, " "height adjustable, " "stepping, " "stand up, " "standing, " "treadmill*, " "walk*, " "elliptical, " "bicycl*, " "pedaling, " "stability ball, " "stability balls, " "exercise ball, " "exercise balls, " "swiss ball, " "swiss balls, " "sit‐to‐stand, " and "sit stand." Results: Nineteen studies (two with school‐aged children) were included in this review. Nine studies used treadmill, three used cycling, one used stepping, and twelve used standing desks. A decrease in sedentary time and an increase in physical activity level and energy expenditure were observed for most of the active workstations. Both the treadmill and the cycle desk improved glycemic control, but the treadmill desk was the only workstation for which improved work performance and help in body‐weight management (body fat percentage, body weight, waist and hip circumference) were reported. Conclusions: Active workstations are a promising solution for decreasing occupational sedentariness. Overall, active workstations have a positive impact on energy expenditure and physical activity in individuals with overweight and obesity.